Development scholastic-methodical complex for independent work student - Aleksandr I. Shimarov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is dedicated to activations of the independent work future specialist. The organization of the work student is Considered on the base specialized scholastic-methodical complex with standpoint of increasing to efficiency of the educational process.